Desenvolvimento e validação de um método analítico para determinação de cobre em cachaça usando FAAS e aplicação no estudo de remoção de cobre em amostras da bebida utilizando bagaço de cana-de-açúcar - André Moreira de Souza (2012)
Sugar cane spirits (Brazilian cachaça) produced in copper stills show better sensorial quality when compared to those produced in pot stills made with other materials such as stainless steel, aluminum and porcelain. The use of equipment in copper stills is favorable for reducing the acidity and the levels of aldehydes and sulfur compounds, which give the drink, unpleasant taste and smell. However, the presence ofhigh concentrations of copper in the drink becomes harmful to human health, since copper is toxic at high concentrations in the body. Among the causes that have been preventing Brazil from achieving higher levels of exportations of cachaça is the difficulty of adjustment to the limits established by regulatory agencies. The maximumconcentration of copper in cachaça allowed by MAPA (Brazilian Ministry of Agriculture, Livestock and Supply) is 5.0 mg L-1. In certain countries the maximum permitted concentration of copper is 2.0 mg L-1. This work presents the development and validation of an analytical method forthe determination of copper in cachaça by using flame atomic absorption spectrometry (FAAS) (Chapter I) and its application in the study of removal of copper in samples of cachaça using residue (bagasse) of sugar cane as an adsorption material (Chapter II). As will be seen in Chapter I, the method developed suggests the directdetermination of the analyte without prior digestion of the sample, only adjusting its alcohol content to 40% (v/v), which reflects the condition used to construct the calibration curve. The validation parameters were evaluated as recommended by the guide of validation of analytical methods from INMETRO, that is: matrix effect, linearity, selectivity, limit of detection (LOD), limit of quantification (LOQ), working range, linear range, precision, accuracy and robustness. Chapter II presents an evaluation of the use of sugar cane bagasse as adsorption material for removing the copper present in commercial samples of cachaça. As will be seen, 1.5 g of bagasse of sugar cane treated with HCl 1.0 mol L-1 was able to reduce the concentration of copper ions to below the levels allowed for export the product (2.0 mg L-1) of 210 ml of an alcoholic solution 40% (v/v) containing 10.0 mg L-1 of copper. A study on the chemical changes in cachaça due to its treatment with sugar cane bagasse was carried out using the technique of GC-MS. As shown in the results, bagasse fromsugar cane does not release any substance in the drink and also does not change its sensory quality.